Free material optimization for plates and shells - Gaile, Stefanie; Leugering, Günter; Stingl, Michael (Proceedings of the 23rd IFIP TC 7 Conference on System Modelling and Optimization, 2009)
In this article, we present the Free Material Optimization (FMO) problem for plates and shells based on Naghdi's shell model. In FMO - a branch of structural optimization - we search for the ultimately best material properties in a given design domain loaded by a set of given forces. The optimization variable is the full material tensor at each point of the design domain. We give a basic formulation of the problem and prove existence of an optimal solution. Lagrange duality theory allows to identify the basic problem as the dual of an infinite-dimensional convex nonlinear semidefinite program. After discretization by the finite element method the latter problem can be solved using a nonlinear SDP code. The article is concluded by a few numerical studies.